Le creux ou la ville en procès chez Rosmarie Waldrop - Vincent Broqua (Anglophonia)
In the texts of the American poet Rosmarie Waldrop’s, the city amounts to a haunting and haunted name, interstices, and empty centres. It is not so much a theme as one of the elements of her poetry of emptiness. Her poems avoid or empty the city, thereby inventing ways to think the city differently. They bring out what is usually left aside, and the margins of the city are therefore "the locus of fertility". In fact, Rosmarie Waldrop’s spectral cities constitute a series of counter-models echoing Paul-Armand Gette’s urban photographs as well as Roland Barthes’ vision of Tokyo.